Beyond quarantine: a history of leprosy in Puerto Rico, 1898-1930s - Levison Julie H. (História, Ciências, Saúde: Manguinhos, 2003)
From biblical times to the modern period, leprosy has been a disease associated with stigma. This mark of disgrace, physically present in the sufferers' sores and disfigured limbs, and embodied in the identity of a 'leper', has cast leprosy into the shadows of society. This paper draws on primary sources, written in Spanish, to reconstruct the social history of leprosy in Puerto Rico when the United States annexed this island in 1898. The public health policies that developed over the period of 1898 to the 1930s were unique to Puerto Rico because of the interplay between political events, scientific developments and popular concerns. Puerto Rico was influenced by the United States' priorities for public health, and the leprosy control policies that developed were superimposed on vestiges of the colonial Spanish public health system. During the United States' initial occupation, extreme segregation sacrificed the individual rights and liberties of these patients for the benefit of society. The lives of these leprosy sufferers were irrevocably changed as a result.